The Effect of Combined Therapy on the Support and Development of Social Skills of people with Multiple Sclerosis in Senior Age - Vostrý, Michal; Fischer, Slavomil; Lanková, Barbora (Neuro endocrinology letters, 2020)
OBJECTIVE: The article contains results of longitudinal research. The aim of the research was to find out how psychomotor therapy with the use of elements of ergotherapy (with the support of cognitive functions; with the support of robotic assisted therapy) on the support and development skills of people with sclerosis multiplex (SM; sclerosis multiplex) in facilities providing social services members of the probands. PROBAND SAMPLE: The research was carried out in 46 probands, with 43.5% of men and 56.5% of women aged 65 - 67 years. The main relevant feature for the selection of probands was the established diagnosis Multiple Sclerosis (according to ICD-10; G35). Another relevant feature for the selection of probands was the length of stay in the facility, which was at least 1 year from the actual start of the facility. The assembled research sample was divided according to other criteria by deliberate selection into the experimental group and the control group. The experimental group participated actively in our intervention and consisted of 23 probands of which 10 were men and 13 were women. The control group only participated in the therapies performed at the facility and did not participate in our intervention. The control group also included 10 men and 13 women. The intervention itself lasted 5 months, three times a week for 40 to 55 minutes. We provided input and output data using a standardized test (FIM test; FIM test; Functional Independence Measure). Subsequent comparison of obtained data between input and output testing was performed by Tuckey HSD test at significance level α = 0.05. RESULTS: The achieved results (at the significance level α = 0.05) show that the experimental group underwent better results in comparison with the initial testing and in comparison with the control group, which rather stagnated in the results, respectively. slightly worsened compared to initial testing.
Keywords: rodina; Multiple Sclerosis; roztroušená skleróza; Cognition; Social Skills; Humans; stárnutí; sociální dovednosti; lidé středního věku; Female; Middle Aged; Aged; Aging; Male; senioři; ženské pohlaví; kognice; Family; lidé; mužské pohlaví